Transportation, childcare, lodging, and meals: Key for participant engagement and inclusion of historically underrepresented populations in the healthy brain and child development birth cohort - Aleksandra E. Zgierska; Tatum Gramly; Nicholas Prestayko; Danielle Symons Downs; Traci M. Murray; Lea G. Yerby; Brittany Howell; Barbara Stahlman; Jennifer Cruz; Arjola Agolli; Holly Horan; Florence Hilliard; et al. (Journal of Clinical and Translational Science, 2024)
Abstract